Influence of Social Media Marketing on Buying Decision Making Process of Consumers - Ms. Riya Goel, Ms. Muskan Diwan (Mathematical Statistician and Engineering Applications, 2022)
The help of various social media like Instagram, Facebook and Twitter gives multiple opportunities to consumers to make the ideal decision for purchasing any product. All of these social media sites play a vital role in influencing consumers' online shopping. Social media sites are flourishing a lot that also provide ideal information to the purchasers regarding the utility and features of the product. The primary goal of the paper is to understand the factors that influence consumers' online purchases. Also, this paper aims to understand the role of social media marketing in influencing consumers' buying behaviour towards online shopping. This paper seeks to comprehend the significance ofsocial media marketing and its effects on consumers' buying behaviour who regularly use various social media sites to buy products. This paper also tries to examine the relationship between social media marketing activities, consumer buying behaviour, and consumer activities among various social media sites.